PENGGUNAAN PSIKOEDUKASI DALAM MENINGKATKAN EFIKASI DIRI BERHENTI MEROKOK PADA SISWA - Isti Antari (Jurnal Kesehatan Madani Medika (JKMM), 2019)
As many as 85% of households in Indonesia are exposed to cigarette smoke, with an estimated 8 smokers dying due to active smokers, one passive smoker dies due to exposure to other people's cigarette smoke, or about 25,000 deaths in Indonesia occur due to secondhand smoke. Bantul District Health Profile 2014 states that in Bantul District epidemiological transition has occurred with the increasing prominence of non-communicable diseases especially hypertension and blood vessels as one of the effects of smoking. The smoking cessation program focuses on behavior change. People with high self-efficacy to stop smoking are ultimately more successful in undergoing a smoking cessation program. The level of self-efficacy to stop smoking can be a predictor of the efforts made to stop smoking. This research is a quasi-experimental approach with pre-post test without control. The study was conducted at SMP X with a sample of 30 students who actively smoked were taken by purposive sampling. The level of self-efficacy to stop smoking is measured before the action and immediately after the action and 3 weeks after the psychoeducation. Descriptive data analysis was performed by presenting frequency distribution data and Wilcoxon Signed Rank Test analysis. Based on the results of the calculation, the Z value obtained is -4.067 where the value <z table 1.96 with p value (Asymp sig 2 tailed) of 0,000 which is less than the set critical limit of 0.05 so it is assumed that there are significant differences between self-confidence to stop smoking the pre-test and post-test groups and it can be concluded that there is an influence of the use of psychoeducation on increasing the self-efficacy of stopping smoking in students.